Satisfaction of orthognathic surgical patients in a Malaysian population - Siow, K.K.; Ong, S.T.; Lian, C.B.; Ngeow, Wei Cheong (Nihon University School of Dentistry, 2002)
Thirty-one patients treated at the Faculty of Dentistry, University of Malaya, were assessed for their satisfaction following orthognathic surgery. The female to male ratio was 22:9 with an age range of 17 to 36. Almost all patients (97) listed appearance as one of their rationales for surgery. More males (78) than females (59) wanted functional improvement, while more females (91) than males (33) hoped for improvement in self-confidence. All patients reported esthetic improvement while 68 each reported improvement in mastication and self-confidence. Slightly more than half (52) chose esthetic improvement as the single most important factor resulting in satisfaction. Almost ninety percent of male patients claimed satisfaction with functional improvement, while 68 of those who found satisfaction in improved self-confidence were females. Eighty-seven percent rated their post-surgical changes as being well accepted by their family. The impact of these findings on the success of the surgery and the need to reinforce verbal communication with printed pamphlets are emphasized.